Early age-stronger base-the advantages of foreign language acquisition in early childhood - Mari Edina (2006)
This thesis has been written to examine the importance of English language teaching and learning in Europe and in Hungary, focusing on the ideal age of the beginners. The writer of this study would like to present her point of view in this complex topic: the importance of learning a foreign language is inevitable. The question when to start, what the advantages and disadvantages of language learning at certain ages are and finding the ideal age and approach are vital questions of the thesis. The research is not based on the perfect mastering of the foreign language, but the positive experience and attitudes very young learners can acquire during the process of acquisition. This process takes place in the kindergarten. The good effects of early English programmes will be demonstrated.